Multivariate classification of provinces of Vietnam according to the level of sustainable development - Truong, Van Canh (Bulletin of Geography. Socio-economic Series, 2021)
The research aims to classify the level of sustainability of 63 provinces in Vietnam upon 24 indicators reflecting three main dimensions of sustainable development by using multivariate classification method for the year 2014-2016. First of all, the principal component analysis (PCA) was applied to group quantitative variables that reflect important aspects of each component of sustainable development of localities in Vietnam into a number of limited dimensions (factors). The results of PCA illustrate 8 principal components in which 3 main components of economic and social pillar, and 2 main components for environmental pillar. After that, the second method was applied by using the hierarchical methods of cluster analysis for the set of 8 principal components conducted by PCA. With the candidate solution divided all of the provinces into 6 clusters, the analysis shows that the higher level of sustainable development belongs to South East, Red River Delta, and North Central, in which 4 provinces of South East (Ho Chi Minh City, Binh Duong, Dong Nai, and Ba Ria – Vung Tau) form a group with the highest level of sustainability. The regions such as South Central Coastal, Highland area, and Mekong River Delta have a medium level; the North midland and mountain areas are regions at the low level of sustainability.